The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jtos.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-stimulated gene 15 (ISG15) restricts Zika virus replication in primary human corneal epithelial cells

Abstract: Purpose: Zika virus (ZIKV) has emerged as an important human pathogen causing ocular complications. There have been reports of the shedding of ZIKV in human as well as animal tears. In this study, we investigated the infectivity of ZIKV in corneal epithelial cells and their antiviral immune response. Methods: Primary human corneal epithelial cells (Pr. HCECs) and an immortalized cell line (HUCL) were infected with two different strains of ZIKV (PRVABC59 & BeH823339) or dengue virus (DENV, serotypes 1-4). Viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 70 publications
(110 reference statements)
1
53
0
Order By: Relevance
“…To our knowledge, our study is the first, to show SARS-CoV-2 antigens in ocular tissue of COVID-19 patients that were procured without PVP-I disinfection treatment, supporting the idea that SARS-CoV-2 could infect corneal epithelial cells. We previously showed that corneal epithelia cells elicit innate responses upon viral stimuli such as ZIKV [ 30 ] or PolyI:C, a viral mimic of dsRNA [ 31 ]. However, further studies are necessary to understand if potential transmission of SARS-CoV-2 through the ocular surface is possible.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our study is the first, to show SARS-CoV-2 antigens in ocular tissue of COVID-19 patients that were procured without PVP-I disinfection treatment, supporting the idea that SARS-CoV-2 could infect corneal epithelial cells. We previously showed that corneal epithelia cells elicit innate responses upon viral stimuli such as ZIKV [ 30 ] or PolyI:C, a viral mimic of dsRNA [ 31 ]. However, further studies are necessary to understand if potential transmission of SARS-CoV-2 through the ocular surface is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, viral infections in humans, including those caused by HSV, herpes zoster virus (HZV), EBV, and CMV, have been shown to increase IOP (5962). Whether the increased IOP observed in our study is due to general viral infection or is specific to ZIKV needs further investigation by challenging the mice with viruses closely related to ZIKV, e.g., dengue virus (25, 63), or unrelated viruses such as VZV. However, based on our in vitro and in vivo findings of susceptibility of TM cells to ZIKV and the induction of an inflammatory response, we propose that ZIKV-induced trabeculitis could be one of the potential mechanisms for increased IOP and glaucomatous pathology (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…All the cells (except C6/36, maintained at 28°C) were maintained at 37°C with 5% CO 2 . The plaque assay was performed using Vero cells as described in one of our recent studies (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first properties attributed to ISG15 was that it could be secreted and act as cytokine (D'Cunha et al, 1996;Dos Santos and Mansur, 2017;Recht et al, 1991). Recently, exogenous free ISG15 has been shown to affect ZIKV replication in corneal cells (Singh et al, 2019). To explore whether extracellular ISG15 plays a role in controlling flavivirus replication in A549 cells, we pre-treated ISG15-deficient cells with 2 µg/ml of recombinant human ISG15 (rISG15) for 12 hours before DV infection.…”
Section: Extracellular Isg15 and Isgylation Deficiency Do Not Affect mentioning
confidence: 99%